What matters most: Randomized controlled trial of breast cancer surgery conversation aids across socioeconomic strata. Issue 3 (10th November 2020) - Durand, Marie‐Anne; Yen, Renata W.; O'Malley, A. James; Schubbe, Danielle; Politi, Mary C.; Saunders, Catherine H.; Dhage, Shubhada; Rosenkranz, Kari; Margenthaler, Julie; Tosteson, Anna N. A.; Crayton, Eloise; Jackson, Sherrill; et al.
Abstract : Background: Women of lower socioeconomic status (SES) with early‐stage breast cancer are more likely to report poorer physician‐patient communication, lower satisfaction with surgery, lower involvement in decision making, and higher decision regret compared to women of higher SES. The objective of this study was to understand how to support women across socioeconomic strata in making breast cancer surgery choices. Methods: We conducted a 3‐arm (Option Grid, Picture Option Grid, and usual care), multisite, randomized controlled superiority trial with surgeon‐level randomization. The Option Grid (text only) and Picture Option Grid (pictures plus text) conversation aids were evidence‐based summaries of available breast cancer surgery options on paper. Decision quality (primary outcome), treatment choice, treatment intention, shared decision making (SDM), anxiety, quality of life, decision regret, and coordination of care were measured from T0 (pre‐consultation) to T5 (1‐year after surgery. Results: Sixteen surgeons saw 571 of 622 consented patients. Patients in the Picture Option Grid arm (n = 248) had higher knowledge (immediately after the visit [T2] and 1 week after surgery or within 2 weeks of the first postoperative visit [T3]), an improved decision process (T2 and T3), lower decision regret (T3), and more SDM (observed and self‐reported) compared to usual care (n = 257). Patients in the Option Grid arm (n = 66) had higher decision process scores (T2 and T3), better coordination of care (12 weeks after surgery or within 2 weeks of the second postoperative visit [T4]), and more observed SDM (during the surgical visit [T1]) compared to usual care arm. Subgroup analyses suggested that the Picture Option Grid had more impact among women of lower SES and health literacy. Neither intervention affected concordance, treatment choice, or anxiety. Conclusions: Paper‐based conversation aids improved key outcomes over usual care. The Picture Option Grid had more impact among disadvantaged patients. Lay Summary: The objective of this study was to understand how to help women with lower incomes or less formal education to make breast cancer surgery choices. Compared with usual care, a conversation aid with pictures and text led to higher knowledge. It improved the decision process and shared decision making (SDM) and lowered decision regret. A text‐only conversation aid led to an improved decision process, more coordinated care, and higher SDM compared to usual care. The conversation aid with pictures was more helpful for women with lower income or less formal education. Conversation aids with pictures and text helped women make better breast cancer surgery choices. Abstract : A paper‐based pictorial conversation aid (pictures plus text) is beneficial to all patients with early‐stage breast cancer and particularly to disadvantaged patients. Between‐surgeon variation suggests that the maximal impact of such interventions requires standardized physician training combined with these interventions.